Pengaruh Pendampingan Diet Terhadap Kepatuhan Diet Dan Kadar Gula Darah Pada Penderita Diabetes Mellitus Di Wilayah Puskesmas Balowerti Kota Kediri - Puguh Santoso; Erna Susilowati (coba, 2018)
Background: Diabetes (DM) is a disease caused by the body is not able to make or use insulin properly, this can lead to complications in the future and cause DM disease suffered more severe. The success of a treatment is determined by the DM patient's attitude toward the treatment. With the compliance of patients with DM then treatment will reach the optimal level, and the quality of health can still be felt. Controlled category of DM is also seen from the results of HbA1C levels, One method that can be used to improve adherence is by counseling dietary behavior. The purpose of the study to determine whether there is Influence Diet Facilitation To Diet Compliance In Diabetes Mellitus patients in Posyandu Elderly "Dharma Husada Insani" in the Working Area Pukesmas Balowerti. Method: The research design used in this research is Quasi experiment with nonequivalent control group design. Population in this research is DM sufferer in Elderly Posyandu "Dharma Husada Insani is Through total technique Sampling obtained by subject amounted to 10 people. Methods for obtaining compliance data with questionnaires, blood sugar levels using HbA1c test. Data were analyzed by bivariate test using simple linear regression, and multivariate using multiple linear regression with 95% confidence level (α = 5%). Results: Mentoring results have a significant association with dietary adherence (p = 0.000). mentoring has no significant relationship to blood sugar levels (p = 0.104). There is a significant association of dietary supplementation to dietary adherence and blood glucose levels together in Elderly Posyandu "Dharma Husada Insani" in the Working Area of ​​Pukesmas Balowerti. (P = 0,000). Conclusion: The conclusion of dietary assistance can improve dietary compliance of Diabetes Mellitus patients, and blood sugar levels can be controlled so as not to cause complications in the future and resulted in DM disease suffered increasingly severe Keywords: Mentoring, Compliance, Blood sugar level.